Răspuns :
39/12-x=9/4
x=39/12-27/12 (am amplificat 9/4 cu 3 )
x=12/12
x=1 (intreg)
raspuns solutia : 1 (intreg)
verificare:
39/12-1(intreg)=39/12-12/12=27/12 (simplificam cu 3) = 9/4
x=39/12-27/12 (am amplificat 9/4 cu 3 )
x=12/12
x=1 (intreg)
raspuns solutia : 1 (intreg)
verificare:
39/12-1(intreg)=39/12-12/12=27/12 (simplificam cu 3) = 9/4
[tex]\frac{39}{12}[/tex] - x= [tex]\frac{9}{4}[/tex]
-x= [tex]\frac{9}{4}[/tex] - [tex]\frac{39}{12}[/tex]
-x= [tex]\frac{27-39}{12}[/tex]
-x= -[tex]\frac{12}{12}[/tex] facem simplificarea
=> -x= -1
Sper să te ajute! ^_^